Manajemen Pepustakaan Sekolah (Studi Manajemen) - Syamsul Hadi (Jurnal Al-Amin: Kajian Pendidikan dan Sosial Kemasyarakatan, 2021)
Management comes from the English word "management" with the verb to manage which generally means to take care of, lead, manage. The word "management" implies leading and leadership. Therefore, school library management implies "leading the school library and "school library leadership." Management is essentially an activity of leading and leadership to achieve organizational goals through activities/moving other people.The library is a minimum standard of school service facilities (Elucidation of the Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System Article 35 Paragraph (1). As a minimum school service facility, the library can be directed to learning activities inside and outside the school environment. the library can be utilized optimally in accordance with the objectives and functions of the school library, it is necessary to have adequate school library management.The school library is a library located in a formal education unit in the primary and secondary education environment which is an integral part of the activities of the school concerned, and is a learning resource center to support the achievement of the educational goals of the school concerned. Specifically, the purpose of the school library is stated in SNI School Libraries 7329-2009, which aims to "provide a learning resource center so that it can help develop and increase interest in reading, information literacy, talents and abilities of students."